PENGARUH TOTAL FENOLTERIPANG PASIR (Holothuria scabra) TERHADAP RESPON IMUN NON SPESIFIK IKAN MAS (Cyprinus carpio) - Achmad Suhermanto (Environmental Research Center (PPLH) of Udayana University, 2013)
AbstractThe aim of the study was to know administration and applications of optimal doses of seacucumber total phenol to increase nonspecific immune response of Carp. Bioactive componentextraction was done by methanol and for further fractionation was dissolved with ethylacetate (v/v). Total phenol identification on ethyl acetate fraction was done to utilize UVVisspectrophotometer and infrared. Total phenol produced was tested on carp withintraperitonial injection, the concentration of 0; 0,09; 0,18; and 0,27 mg phenols/kg fish..Challenge be done utilizes A. hydrophila (107cell/ml) with immertion method. Statisticalanalysis involved one-way analysis of varians (ANOVA) by minitab 14. The level ofsignificance were expressed as P-value less or greater than 0.05.The result of hematological parameters showed that hematocrit (PVC), hemoglobin,erythrocytes, lymphocyte pre infection was increased significantly and post-bacterial wasdecreased significantly (p<0.05). Leukocytes, Neutrophils pre-and post-infection weresignificantly increased (p<0.05). Eosinophils, monocytes pre-and post bacterial infectionwere not differ significantly between treatment (p<0.05).